Protect with Plywood - Hal S. Knowles, III; Kathleen C. Ruppert; Karla A. Lenfesty; Barbara Haldeman (EDIS, 2007)
ABE-376, a 2-page fact sheet by Hal S. Knowles, III, Kathleen C. Ruppert, Karla A. Lenfesty, and Barbara Haldeman, is part 3 in the Education + Action = Wind Damage Mitigation series. It contains information on the proper tools and safety regarding installing/putting up plywood shutters. Published by the UF Department of Agricultural and Biological Engineering, November 2005.